Experimental Insights Into the In Situ Formation and Dissociation of Gas Hydrate in Sediments of Shenhu, South China Sea - Zhang, Qian; Qin, Xuwen; Zhang, Hong; Dong, Yanhui; Lu, Cheng; Li, Shouding; Xiao, Luokun; Ma, Chao; Bian, Hang (Frontiers in Earth Science, 2022)
Natural gas hydrates as sustainable energy resources are inherently affected by mineral surfaces and confined spaces in reservoirs. However, the habits of hydrates in geological sediments are still an open question. In this work, we systemically studied the process of hydrate formation and dissociation in sediments from the Shenhu area of the South China Sea to examine the evolution of hydrate saturation and permeability in sediments, and their relationship. Characterization of samples indicates that sediments of the Shenhu area are mainly composed of clay and fine sand grains and provide a large amount of nanopores for hydrate accumulation. For in-situ observations enabled by low-field nuclear magnetic resonance methods, the formation of hydrates shows a different kinetic behavior with an induction time compared to hydrate dissociation. Estimated by variations of hydrate saturation (%) over time, the rate of hydrate formation is around 12%/min, while the dissociation rate increases to 3%/min with the higher temperature. With the presence of hydrates, pore space and thus permeability of sediments decreased obviously by one and three orders of magnitude when the hydrate saturation is 20% and 45%, respectively. Compared to models with the assumption of grain-coating and pore-filling hydrates, the tendency of permeability evolution from NMR measurements is between fitted lines from models. It highlights that the existing models considering a single pattern of hydrate growth cannot precisely describe the relationship of permeability and hydrate saturation. Hybrid hydrate habits coexist in sediments resulting from heterogeneous pore structures and thus complex gas-water distributions.